Fungicide resistance profile and genetic structure of Botrytis cinerea from greenhouse crops in Cyprus - Kanetis, Loukas; Christodoulou, Souzana; Iacovides, Tefkros A. (My University, 2017)
Botrytis cinerea is a complex species prone to fungicide resistance and characterized by enormous genetic diversity. During 2013, 220 B. cinerea isolates causing gray mold were collected from greenhouse-grown crops in the regions of Ammochostos, Larnaca, and Limassol (Cyprus). Sensitivities of the sampled populations to seven botryticides with different modes of action were screened in vitro. The results of this in vitro screening highlighted the widespread phenomenon of fungicide resistance in greenhouses, since only 8.6 % of the isolates were sensitive to all botryticides. Resistance to thiophanate-methyl was the most prevalent, with frequencies ranging from 53.8 % to 80 %. Similarly, high resistance frequencies were observed for pyraclostrobin (27.1 to 78.9 %) and boscalid (28.2 to 66.2 %). Multiple fungicide resistant phenotypes were predominant, covering 67.3 % of the population, with frequencies of 80.0, 37.5, 53.8, 83.1, and 60.2 % in cucumber, eggplant, green bean, strawberry, and tomato, respectively. No fludioxonil-resistant isolates were observed. Botrytis cinerea and Botrytis group S genotypes comprised the gray mold population. B. cinerea was predominant within cucumber, eggplant and strawberry, whereas both genotypes were in equilibrium in green bean and tomato. However, Botrytis group S was found in all hosts. B. cinerea was the most prevalent in the majority of fungicide resistance phenotypes from strawberry, while genotype distributions within tomato were generally more balanced. B. pseudocinerea was not detected in the sampled population. Overall, frequency of the mating type allele MAT1–1 was higher to MAT1–2, underlying their unequal distribution in the population. However, cases of 1:1 distribution were apparent within particular subpopulations, suggesting that mating in the field cannot be excluded.
Keywords: Botrytis group; Mating type; Botrytis pseudocinerea; Fungicide resistance; Strawberry; Tomato